Co-creation of experiences in museums by people with sensory impairments - Mesquita, Susana Maria Vasconcelos (2024)
Despite the growing concern with social inclusion, people with sensory impairments (PwSI), such as those regarding vision or hearing, are one of the most marginalized groups. Museums, as important cultural spaces with social functions, are trying to adopt more inclusive and participatory practices to encourage the co-creation of experiences for people with disabilities (PwD). Yet, there are still constraints, which restrict PwD from fully enjoying museums. In spite of the high number of PwSI, there is a lack of research regarding how they co-create their museum experiences, on factors that may stimulate or constrain that co-creation, as well as on the corresponding outcomes. This thesis aims to analyse the influence of antecedents that interfere in the cocreation of PwSI’ museum visit experiences, regarding both antecedents related to the visitors and the museums, as well as examine the way PwSI co-create in museums, and the benefits they obtain from that co-creation, namely perceived value, satisfaction and loyalty. An extensive literature review was carried out allowing to propose a conceptual model to address several research gaps identified. The model encompasses antecedents, co-creation and outcomes obtained by PwSI in this co-creation in museums, suggesting that the antecedents, when identified and worked on, can boost these visitors’ co-creation of experiences in museums, and that this cocreation can have relevant positive outcomes. Empirical research was undertaken adopting a mixed methods approach. First, focus groups were carried out to more deeply understand how PwSI co-create their experiences in museums and the role of several antecedents in that cocreation, as well as to obtain insights on measures for assessing the constructs under analysis. After, to test the model proposed, a quantitative study was carried out based on a questionnaire survey. A total of 675 valid questionnaires were obtained, 254 from PwSI and 421 from people without sensory impairments. Data were analysed using the software Statistical Package for the Social Sciences and the SmartPLS. Multiple linear regressions and partial least squares structural equation modelling (PLS-SEM) were undertaken to test the hypotheses and compare perceptions of PwSI and people without disabilities. Results reveal that antecedents, both related to visitors and to museums, have a significant impact on various dimensions of PwSI’ co-creation in museums. Also, specific dimensions of co-creation influence perceived value dimensions, and significant indirect effects on satisfaction and loyalty were found. The condition of having a sensory impairment was found to have positive significant impacts on several dimensions of co-creation and on perceived emotional, learning and social value, highlighting the relevance of highly and meaningful cocreative experiences for these specific visitors. Theoretical and managerial contributions for museum management are drawn to foster more inclusive valueadded experiences for PwSI.